Safe in the first attempt: teaching neonatal airway management. Issue 3 (June 2022) - Garcia-Marcinkiewicz, Annery G.; Matava, Clyde T.
Abstract : Purpose of review: Quick and precise facemask ventilation and tracheal intubation are critical clinical skills in neonatal airway management. In addition, this vulnerable population requires a thorough understanding of developmental airway anatomy and respiratory physiology to manage and anticipate potential airway mishaps. Neonates have greater oxygen consumption, increased minute ventilation relative to functional residual capacity, and increased closing volumes compared to older children and adults. After a missed airway attempt, this combination can quickly lead to dire consequences, such as cardiac arrest. Keeping neonates safe throughout the first attempt of airway management is key. Recent findings: Several techniques and practices have evolved to improve neonatal airway management, including improvement in neonatal airway equipment, provision of passive oxygenation, and closer attention to the management of anesthetic depth. The role of nontechnical skills during airway management is receiving more recognition. Summary: Every neonatal intubation should be considered a critical event. Below we discuss some of the challenges in neonatal airway management, including anatomical and physiological principles which must be understood to approach the airway. We then follow with a description of current evidence for best practices and training.